Age and Metallicity Analysis of the Small Magellanic Cloud from Star Clusters - Parisi, María Celeste (2013)
Fil: Parisi, María Celeste. Universidad Nacional de Córdoba. Observatorio Astronómico de Córdoba; Argentina.